ASSOCIATION BETWEEN CAGA AND VACA GENES OF HELICOBACTER PYLORI AND ENDOSCOPIC LESIONS IN PATIENTS WITH GASTRITIS (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the association between H. pylori infection and upper gastrointestinal endoscopic lesions at Van Hanh General Hospital.Methods: A cross-sectional descriptive study was conducted on 73 patients with gastritis who underwent upper gastrointestinal endoscopy at Van Hanh General Hospital from June 2025 to February 2026. H. pylori infection was diagnosed using the rapid urease test and PCR from gastric mucosal biopsy specimens. Endoscopic lesions were evaluated through upper gastrointestinal endoscopy.Results: The prevalence of H. pylori strains carrying the cagA gene was 74%. Regarding the vacA gene, the s1m2 genotype accounted for 54.8%, s1m1 for 41.1%, and s2m2 for 4.1%, with no s2m1 recorded. Infection with cagA-positive H. pylori was associated with hemorrhagic gastritis (OR=5.58, p=0.032). Infection with H. pylori carrying the cagA gene, the vacA s1m1 genotype, and a BMI < 23 were associated with a significantly reduced risk of gastroesophageal reflux disease. Multivariate regression analysis showed that infection with H. pylori carrying the cagA gene was independently associated with a decreased risk of gastroesophageal reflux disease (OR=0.072; p=0.003).Conclusion: H. pylori strains carrying the cagA gene and high-virulence vacA genotypes are predominant; notably, the cagA gene both increases the risk of hemorrhagic gastritis and independently reduces the risk of gastroesophageal reflux disease.
Keywords: cagA, vacA, hemorrhagic gastritis, gastroesophageal reflux disease, H. pylori.